World Bank CCS Program Activities in Botswana – Results and Lessons Learned - Beck, Brendan; Kulichenko-Lotz, Natalia (Elsevier, 2018)
The World Bank Carbon Capture and Storage Trust Fund (CCS TF) was established in 2009 to support CO2 capture and storage (CCS) capacity and knowledge building in developing countries. CCS TF Phase 1 support for CCS in Botswana included an allocation of USD 1.4 million and had the objective of supporting the Government of Botswana in the following areas: 1. Identifying potential geological reservoirs that can be utilized to store CO2 captured from coal-fired power plants; 2. Evaluating institutional and regulatory arrangements for CCS deployment in the country and recommendations for reinforcing institutional capacity; and 3. Providing training, education and capacity building at all stages throughout implementation, including a Study Tour for key individuals.